PATTERN OF ANTIHYPERTENSIVE DRUG UTILIZATION IN A TERTIARY CARE HOSPITAL - JOHAN PANDIAN J,; MANIMEKALAI K,; VELVIZHY R, (International Journal of Pharma and Bio Sciences, 2015)
Drug Utilization research is defined by WHO as “the marketing, distribution, prescription and use of drugs in a society, with special emphasis on the resulting medical, social and economic consequences”. The treatment for hypertension involves the use of many new antihypertensive drugs. So this study was done in order to know the current prescribing trend of antihypertensive agents The study was carried out from January 2011 to December 2011. Patients above 18 years of age who have been diagnosed with hypertension according to JNC VII classification were included. All the parameters were noted down in the specially structured case Proforma. In a total of 230 prescriptions with essential hypertension the male/female ratio was almost equal. 155 cases were on mono therapy (MT) (67.3%). 20 cases were on multiple drug therapy (MDT) (8.6%). 55 cases were on fixed dose combinations (FDC) (23.9%) A total of 32.5% cases received more than one drug for hypertension. The most commonly prescribed antihypertensive medications were in the order of CCB’s (30.43%), ACEI’s (30.43%), ARB’s (29.13%), β blocker’s (23.04%) and lastly the diuretics (19.56%). The drug-prescribing trend of anti-hypertensive agents by physicians at this tertiary care hospital is rational and it is in accordance with JNC guidelines.